Determination of the diffusion coefficient in sodium chloride solution at different concentrations - Antonio Marcos de Oliveira Siqueira; Gabriel Luz Chaves; Joyce de Souza Tanure; Luana Ventura Dutra; Nathan Barros de Souza; Thomás Corrêa Vianna (The Journal of Engineering and Exact Sciences)
Phenomena of diffusion are present in several industrial phenomena and therefore need to be properly studied and understood. The study of liquid-liquid diffusion allows to perfect and model several industrial systems. The development of instruments capable of doing this study allows to create methodologies for the development of students of the most diverse engineering. This work employed the study of the diffusion phenomena in a diffusion cell constructed by the authors themselves based on materials found in laboratories, trying to calculate the diffusion coefficient of a solution of sodium chloride in water through the variation of conductivity. The diffusion coefficients obtained presented values in the same order of magnitude in relation to the experimental values reported by other authors and with low experimental error.